2011
DOI: 10.5937/ratpov1102275m
|View full text |Cite
|
Sign up to set email alerts
|

Genetic background and agronomic value of leaf types in pea (Pisum sativum)

Abstract: RONO: 00Pea (Pisum sativum L.) has a compound leaf like many other legume species. The 'semi-leafless' pea (afaf tltl), with all leaflets transformed into tendrils, is considered one of the most important achievements in pea breeding, due to a significantly enhanced standing ability and equally efficient dry matter production in comparison to normal-leafed genotypes (AFAF TLTL). 'Semi-leafless' cultivars provide high and stable grain yield and are dominant in the modern dry pea production worldwide. There are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 33 publications
(34 reference statements)
1
25
0
Order By: Relevance
“…In that way, it was confirmed that any morphological change in field pea plants, such as short stem or afila leaf type, significantly contributes to increased seed yield (Mikić et al, 2011b). This has highly practical implications in field pea breeding by developing novel cultivars with essentially transformed plant architecture in comparison to traditional field pea landraces with long stems and high seed yield losses during the harvest (Mihailović & Mikić, 2010).…”
Section: Introductionmentioning
confidence: 89%
“…In that way, it was confirmed that any morphological change in field pea plants, such as short stem or afila leaf type, significantly contributes to increased seed yield (Mikić et al, 2011b). This has highly practical implications in field pea breeding by developing novel cultivars with essentially transformed plant architecture in comparison to traditional field pea landraces with long stems and high seed yield losses during the harvest (Mihailović & Mikić, 2010).…”
Section: Introductionmentioning
confidence: 89%
“…However, grain yields in the current study are lower than those of the traditional grain legumes in Serbia, such as field pea, varying between 3348 and 5252 kg ha −1 (Mikić et al 2011c). This still represents a significant barrier to higher adoption of common vetch by Serbian farmers.…”
Section: Grain Yieldmentioning
confidence: 91%
“…One of the alternative types of forage pea cultivars are those with an acacia leaf type (Figure 11, middle), characterized by a large number of leaflets and no tendrils. Although theoretically expected to have an increased leaf proportion and thus better forage quality, they are extremely prone to lodging, suffering either from low seed yield or large seed losses during harvest, and consequently their successful commercialisation is questionable (Mikić et al, 2011c). An additional targeted trait in all modern forage pea breeding programs is reliable seed yield.…”
Section: B Ideotypes In Breeding Forage Annual Legumesmentioning
confidence: 99%